Ownership structure of family-owned firms and debt financing. evidence on shari’ah-compliant firms in Malaysia - Haron, Razali (International Islamic University Malaysia, 2017)
This study examines the impact of ownership structure on the debt financing of 556 Shari’ah compliant firms in Malaysia from 2000-2015. This study reveals that the nature of family-owned firms does have great influence in the debt financing decisions and being closely guided by the Shari’ah principles with the restriction imposed on the debt consumption level allowed seem to have significant effect on the debt financing of Shari’ah-compliant firms understudy as well. Fear of the dilution of controlling power over the firms for these family owned and the characteristics of Shari’ah-compliant being governed by certain Shari’ah regulation have significant influence on debt consumption in the capital structure. Certain significant determinants seem to enhance the unique nature of these firms regarding the debt financing decision. This study contributes to the literature by providing insights of the factors affecting the debt financing of family owned, Shari’ah-compliant firms in Malaysia.